Adenoid ameloblastoma with dentinoid: A rare hybrid odontogenic tumor - Tabita J. Chettiankandy; Sanpreet S. Sachdev; Prajwalit P. Kende; Manisha A. Sardar; Reshma Saju (Indian Journal of Pathology and Microbiology)
Background: Adenoid ameloblastoma with dentinoid (AAD) is a hybrid odontogenic tumor comprising histopathological presentation of ameloblastoma (AM) and adenomatoid odontogenic tumor (AOT) along with extracellular dentinoid material. Case Presentation: A 35-year-old female reported an asymptomatic swelling in the left mandibular posterior region. Histopathological examination revealed composite features of AM with AOT along with dentinoid material, which stained positively with Van Gieson and trichrome stains. Conclusion: The present case report serves to add further to the modicum of literature reports pertaining to AAD, which may gain recognition as a distinct entity in future World Health Organization (WHO) classification of odontogenic tumors.